Titus Andronicus - Shakespeare, William (Cambridge University Press, 1994)
A volume in The New Cambridge Shakespeare, newly edited to the meticulous standard for which this series has become known, this edition of Titus Andronicus includes an extensive introduction that leads the reader through the full spectrum of contemporary criticism of the play, major modern productions, and its performance history. Appendices explore how the play might have been performed at the Rose playhouse, which has been recently excavated, and how it could have been adapted for a touring company of fourteen men and boys.